Incidencia del perfil profesional de los alcaldes en la gestión y administración institucional del GAD Machala periodo 2015-2022 - Hidalgo Sandoya, Jean Michael; Zhinin Alvarez, Nathaly Paulette (Machala: Universidad Técnica de Machala, 2023)
The present research work analyzes the professional profile of the mayors and the incidence before the management and administration of the Municipal Government of Machala in the periods 2014-2019, 2019-2023. The code of democracy and the constitution protect political participation, however, this does not take into account the academic preparation or the degree of knowledge of a candidate. It´s important to emphasize that in the 2023 sectional elections in the capital city of the Province of El Oro, there were 14 candidates in search of the mayoralty. Politics is a field where the human being since its inception has been involved, an investigation carried out in 2021 where Weber refers to it is mentioned that the political field is made for the execution of human actions, Therefore, the emergence of new faces, ideologies and ways of doing politics will continue. The specific objectives of this research aim to establish the impact of the professional profile of mayors insocial management, at the same time, it seeks to determine how the profile around the management influences infrastructure and basic services, it is also aimed at identifying the different human and professional characteristics that a candidate for mayor must have. On the other hand, it is necessary to mention that the research is based on the plane of structural functionalism, approach that clarifies the interaction of human beings and the roles they play within a society, at the same time, there is an analysis of the systems around power and politics. Nevertheless, it should be noted that the typology of the research is basic with a mixed methodology, where techniques such as the survey, interview and literature review were used, making use of the necessary tools such as, the questionnaire, books, articles, magazines and a structured questionnaire for the interviews. As a result of the research, it was established that there is an impact of the professional profile in public management in the social area; on the other hand, it was determined that academic preparation has a high degree of influence on management with reference to infrastructure and basic services. Leadership, professionalism, honesty and youth are characteristics that were identified as necessary to be candidates for mayor of the city of Machala. Consequently, in view of the results of the research, the proposal for the improvement of the professional profile of political actors was established. through training around management, governance and governance, which aims to improve the professional profile of political actors, consequently raise the level of public management of the Municipal GAD of Machala.
El presente trabajo de investigación analiza el perfil profesional de los alcaldes y la incidencia ante la gestión y administración del GAD Municipal de Machala en los periodos 2014-2019, 2019-2023. El código de la democracia y la constitución amparan la participación política, sin embargo, esta no toma en cuenta la preparación académica o el grado de conocimiento de un candidato. Es importante recalcar que en las elecciones seccionales 2023 en la urbe capital de la Provincia de El Oro, existieron 14 candidatos en búsqueda de la alcaldía. La política es un campo donde el ser humano desde sus inicios ha está involucrado, en una investigación realizada en el 2021 donde hace referencia a Weber se menciona que el campo político está hecho para la ejecución de acciones del ser humano, por lo tanto, se mantendrá la aparición de nuevos rostros, ideologías y formas de hacer política. Los objetivos específicos de la presente investigación pretenden establecer la incidencia del perfil profesional de los alcaldes en la gestión social, a la vez, buscan determinar cómo influye el perfil entorno a la gestión referente a la infraestructura y los servicios básicos, también se direcciona a la identificación de las diferentes características humanas y profesionales que debe tener un candidato a alcalde. Cabe mencionar que la investigación se fundamenta en el plano del funcionalismo estructural, enfoque que esclarece la interacción de los seres humanos y los roles que cumplen en una sociedad, también se analizan los sistemas entorno al poder y la política. Al contar con hipótesis y estas deben comprobarse o refutarse esta investigación se asienta en el enfoque epistemológico hipotético-deductivo, por otro lado, la tipología de la investigación es básica con una metodología mixta, donde se utilizaron técnicas como la encuesta, la entrevista y la revisión bibliográfica usando herramientas necesarias como el cuestionario, libros, artículos, revistas y un cuestionario estructurado para las entrevistas. La investigación ha permitido establecer que sí existe incidencia del perfil profesional en la gestión pública entorno al área social, por otro lado, se pudo determinar que la preparación académica influye en la gestión, facilitando la concreción de infraestructuras y provisión de servicios básicos. El liderazgo, el profesionalismo, la honestidad y la juventud son características que se identificaron como necesarias para ser candidatos a alcaldes de la ciudad de Machala. Consecuentemente ante los resultados de la investigación se estableció la propuesta para el mejoramiento del perfil profesional de actores políticos mediante capacitaciones entorno a la gestión, gobernanza y gobernabilidad, con lo cual se pretende mejor el perfil profesional de los actores políticos, consecuentemente elevar el nivel de gestión pública del GAD Municipal de Machala.
Keywords: ALCALDE; ACTOR POLITICO; GESTION PUBLICA; ADMINISTRACION PUBLICA